Educational Games in English Learning Class X Students Department of Electrical Engineering SMK Negeri Sukoharjo - Hadiyastama, Muhammad Fu'ad; Yulianti, Tien; Firdaus, Rangga (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2024)
The aim of this research is to utilize educational game learning media to help students have competence in English. Understanding English allows individuals to communicate with people from various backgrounds and cultures. 21st century skills are an integration of knowledge skills and attitudes as well as mastery of ICT development through; critical thinking skills and problem solving skills, communication skills, creativity and innovation skills, and collaboration skills. Through this method students are invited to actively participate in the learning process and train their ability to think critically. The results of the implementation of the use of educational game learning media are expected to be able to develop students' competence in English so that students are able to compete in the world of work. This research stage refers to the six steps in developing the ASSURE model. Analyze learners, State Objectives, Select Methods, Media, and Materials, Utilize Media and Materials, Learner Participation, Evaluate and Revise. Grades are divided into three categories A (Very Good), B (Good), and C (Poor). Educational games are an alternative learning media that can help students have competence in learning English.